ICRISAT and CGIAR Champion Multifunctional Landscapes Approach at AERA Annual Conference - Kumar, Shalander; Singh, Ramesh; Das, Abhishek; Anantha, K. H.; Nukala, NagarjunaReddy (International Crops Research Institute for the Semi-Arid Tropics, 2025)
​At the 33rd Annual Conference of the Agricultural Economics Research Association (AERA), held at ICAR–National Academy of Agricultural Research Management (ICAR-NAARM), Hyderabad, ICRISAT and CGIAR’s Multifunctional Landscapes (MFL) Science Program convened a high-level session on “Scaling Pathway for Multifunctional Landscapes Approach for Transforming Agri-Food Systems.”